The neurological work of Artur Galcerán i Granés (1850–1919) - A. Arboix (Neurología (English Edition), 2011)
Introduction: To analyze the neurological work of Artur Galcerán i Granés (Girona 1850-Barcelona 1919) founder of the Society of Psychiatry and Neurology of Barcelona in 1911. Methods: We performed a literature search using MEDLINE from the keywords “Galceran Granés” and “Society of Psychiatry and Neurology of Barcelona”, using the doctoral thesis of M. G. Fabregas Camps: “History of Neurology in Catalonia. From 1882 to 1949” and original historical bibliographical sources of the Library of the Academy of Sciences Mèdiques de Catalunya i Balears. Results: Artur Galcerán i Granés was a disciple of the school of psychiatry of Dr. Joan Giné i Partagàs. His highlighting neurological work was: 1) “Some static and dynamic inferences about the brain, which may serve to clarify the concept of localization”, 2) “Treatment of epilepsy” and 3) “Neuropathology and General Psychiatry”. He was editor of “Archivos de Terapeútica de las enfermedades nerviosas y mentales” and “Anales de la Sociedad de Psiquiatría y Neurología”. He was director of the mental asylum in Sant Boi of Llobregat and Pere Mata of Reus. In 1911 he founded the first Catalan and Spanish neurological society in Barcelona. Conclusions: The neurological work of Artur Galcerán i Granés is remarkable and significant. He was the founder of the first Catalan and Spanish neurological society: The Society of Psychiatry and Neurology of Barcelona in 1911, the forerunner of the Catalan Society of Neurology. Resumen: Introducción: Analizar la faceta neurológica que es poco conocida de Artur Galcerán i Granés (Girona 1850-Barcelona 1919), fundador de la Sociedad de Psiquiatría y Neurología de Barcelona en 1911. Fuentes: Se efectúa una búsqueda bibliográfica mediante MEDLINE sin límite de fecha a partir de las palabras clave: “Galceran Granés” y “Society of Psychiatry and Neurology of Barcelona”, utilizando también la tesis doctoral de M. G. Fabregas Camps: “Història de la Neurologia a Catalunya. De l’any 1882 a l’any 1949”, y de fuentes bibliográficas históricas originales de la Biblioteca de la Acadèmia de Ciències Mèdiques de Catalunya i Balears de Barcelona. Desarrollo: Artur Galcerán i Granés se denominaba “neurólogo y mentalista”. Discípulo de la escuela de Psiquiatria de Joan Giné i Partagàs. Su obra neurológica fue notable, destacando: 1)“Algunas inducciones sobre estàtica y dinàmica del cerebro, que pueden servir para el esclarecimiento del concepto de localización”; 2) “Tratamiento de las epilepsias”, y 3) “Neuropatología y Psiquiatría generales”. Dirigió “Archivos de Terapéutica de las enfermedades nerviosas y mentales” y “Anales de la Sociedad de Psiquiatría y Neurología”. Fue director del sanatorio mental de Sant Boi de Llobregat y de Pere Mata de Reus. Fundó la primera sociedad neurológica catalana y española en Barcelona en el año 1911. Conclusiones: La faceta neurológica de A. Galcerán i Granés es remarcable y significativa. Fue el fundador de la primera sociedad neurológica catalana y española: la Sociedad de Psiquiatría y Neurología de Barcelona en el año 1911 precursora de la Societat Catalana de Neurologia. Keywords: Galcerán i Granés, History, Neurology, The Barcelona Society of Psychiatry and Neurology, Neurology Society, Palabras clave: Galcerán i Granés, Historia, Neurología, Sociedad de Psiquiatía y Neurología de Barcelona, Sociedad neurológica